Pre-service Teachers’ Perception regarding Reflective Competence - Mihaela Voinea; Anastasia Mălina Cioloca; Andreea Șițoiu (Revista Românească pentru Educaţie Multidimensională, 2025)
Teachers’ reflective competence is an important issue in initial and continuous teacher training nowadays. Several educational policy documents such as OECD, 2019; EUA, 2021; EUA 2023; ME, 2024; and recent research on “future skills” (Ehlers, 2022) underline that in the context of reforming education systems, the impact of digitization, reflection, reflectivity and reflexivity, is a key source for optimizing educational practices. Starting from the premise that reflective competence is one of the important “future skills” in the teaching career, the present research aimed to investigate pre-service teachers' perceptions of reflective competence (“students’ eyes” according to Brookfield's theory of critically reflective teacher). The sample consisted of 327 student-teachers at the bachelor's and master's levels (initial training). A questionnaire was used to explore the way pre-service teachers see the reflective competence in teaching practices of their teachers. The data resulting from the analysis of the questionnaire highlighted that reflective competence is formed during university education (initial teacher training) and is facilitated by the observation of specific behaviors of some reflective teachers (r = .52, p < .001). Also, 27% of the variability in the development of pre-service teachers' self-reflexivity competencies is due to teachers' perceived reflexivity in the context of instructional-educational activities. Another practical conclusion is that reflexivity needs to be more 'visible' in the behavior of teachers and mentors in teaching practice in order to help pre-service teachers develop their reflective competence.
Keywords: teacher’s reflexivity; reflective competence; pre-service teachers’ perception